Numerical analysis of Dielectric Barrier Discharge - Roveda, Fabio <1984> (Alma Mater Studiorum - Università di Bologna, 2012)
A numerical investigation of dielectric barrier discharge aimed to simulate the electro hydro dynamic interaction is presented. A discharge drift diffusive model according to the Townsend avalanche is described and used to duplicate the plasma kinetics of a DBD actuator. The discharge characteristics dependence upon dielectric material and applied voltage are simulated and the EHD force field according to a simplified approach is presented and discussed. The coupling of DBD results with a fluid dynamic code is also shown. Finally, a new non invasive diagnostic technique for EHD interaction based on Schlieren imaging is computationally validated.